An antimony-based liquid metal battery and a method of making the same
Patent Information
- Application Number
- CN202611052750.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-30
AI Technical Summary
虽然这种方法能起到一定作用,但是由于液态金属的表面张力较大,且与石墨的浸润性较差,因而极易在石墨表面团聚成球,缩短正负极间距;同时电解质极易渗入下方将正极和石墨隔开,造成接触不良,降低电池能量效率和电压效率,严重时会将正极“抬起”引发电池短路失效
本发明提出的锑基液态金属电池采用Fe-Sb正极可以避免向锑基液态金属电池中引入其他内衬减少了接触界面和接触阻抗,既节省了成本又提升电压效率和电池稳定性;电池在充放电过程中铁不参与电化学反应,且铁的熔点较高,加入的适量铁粒会弥散分布在锑熔体中,形成“锑包铁”的形态,可以增加正极反应面积,加入的铁通过与锑形成熔体,抑制金属锑对不锈钢的腐蚀;同时铁的电导率优于锑,增加了正极的导电性,因此可以提升电池电压效率。
Smart Images

Figure CN123018175A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of liquid metal battery technology, and in particular to an antimony-based liquid metal battery and its preparation method. Background Technology
[0002] Liquid metal batteries, as an emerging electrochemical energy storage technology, have attracted widespread attention since their inception. They utilize alkali or alkaline earth metals with low density and electronegativity as the negative electrode, a metal or metalloid with higher density and electronegativity as the positive electrode, and a molten inorganic salt as the electrolyte. Based on the density difference between the positive and negative electrodes and the electrolyte, and their immiscibility, they automatically separate into three layers. During discharge, the negative electrode metal ions pass through the electrolyte to the positive electrode, where they undergo an alloying reaction; the charging process is the reverse. Antimony metal has a high specific capacity (660 mAh g⁻¹). -1 Antimony is a common positive electrode material in liquid metal batteries. However, at high temperatures, antimony readily reacts with the stainless steel casing of the battery, causing corrosion and leakage, thus affecting battery stability. Current solutions involve adding a graphite liner inside the battery casing to prevent direct contact between antimony and the casing. While this method has some effect, the high surface tension of liquid metal and its poor wettability with graphite make it prone to agglomerating into spheres on the graphite surface, shortening the distance between the positive and negative electrodes. Simultaneously, the electrolyte easily seeps below, separating the positive electrode from the graphite, causing poor contact, reducing battery energy efficiency and voltage efficiency, and in severe cases, "lifting" the positive electrode, leading to short-circuit failure. Summary of the Invention
[0003] The purpose of this invention is to address the aforementioned shortcomings of existing technologies by proposing an antimony-based liquid metal battery and its preparation method. This invention improves the stability of antimony-based batteries and simultaneously increases battery voltage efficiency without introducing an internal liner inside the battery casing.
[0004] The first objective of this invention is to provide a method for preparing an antimony-based liquid metal battery, comprising the following steps: S1. Place a mixture of iron particles and antimony particles in a stainless steel battery casing as the positive electrode material, and then heat it in an inert atmosphere at 700-730 °C for 30-60 min to ensure that the positive electrode material is fully melted and spread out at the bottom of the battery casing. After the heat preservation is completed, cool it with the furnace to obtain the Fe-Sb positive electrode. S2. Melt the electrolyte material by heating and pour it into the stainless steel battery casing; S3. Assemble the negative electrode current collector loaded with metallic lithium and the battery top cover onto the stainless steel battery casing, and then allow it to cool naturally; wherein the battery top cover and the stainless steel battery casing cooperate to form a closed space.
[0005] Furthermore, the iron particles are 20–50 mol of a mixture of iron particles and antimony particles.
[0006] Furthermore, the distance between the positive and negative electrodes is controlled at 12–15 mm.
[0007] Furthermore, the electrolyte material is a LiF-LiCl-LiBr electrolyte.
[0008] Furthermore, the negative electrode current collector loaded with lithium metal is 14 mm thick. A 2 mm thick lithium metal strip is wound around the negative electrode current collector.
[0009] Furthermore, calculate the required amount of metallic lithium according to the Li / Sb molar ratio of 3:1.
[0010] Furthermore, it is kept at an inert atmosphere of 700–730 °C for 30–60 min.
[0011] Furthermore, the required mass of electrolyte is calculated based on the distance between the positive and negative electrodes, and the electrolyte mass is controlled to just submerge the upper surface of the negative electrode current collector. The calculation formula is m = 0.8ρπr 2 (h+d), where m is the electrolyte mass, the stainless steel battery casing is cylindrical, r is the battery casing radius, h is the distance between the positive and negative electrodes, d is the thickness of the negative electrode current collector, and ρ is the electrolyte density. Since the current collector itself occupies a certain volume, the actual added electrolyte mass is 80% of the theoretical value.
[0012] A second objective of this invention is to provide an antimony-based liquid metal battery prepared by the method described above.
[0013] The technical solution of this invention has the following advantages: The antimony-based liquid metal battery proposed in this invention uses an Fe-Sb cathode, which avoids introducing other liner into the antimony-based liquid metal battery, reducing the contact interface and contact impedance, thus saving costs and improving voltage efficiency and battery stability. During the charging and discharging process, iron does not participate in the electrochemical reaction, and iron has a high melting point. The appropriate amount of iron particles added will be dispersed in the antimony melt, forming an "antimony-encased iron" morphology, which can increase the cathode reaction area. The added iron inhibits the corrosion of stainless steel by forming a melt with antimony. At the same time, the conductivity of iron is better than that of antimony, which increases the conductivity of the cathode, thus improving the battery voltage efficiency. Attached Figure Description
[0014] Figure 1 The voltage efficiency of the liquid metal battery proposed in this invention at different current densities; Figure 2 The long-cycle performance of the antimony-based liquid metal battery prepared in Example 1; Figure 3The long-cycle performance of the antimony-based liquid metal battery prepared in Example 2; Figure 4 The long-cycle performance of the antimony-based liquid metal battery prepared in Example 3; Figure 5 To demonstrate the long-cycle performance of the pure antimony-based liquid metal battery prepared in Comparative Example 1; Figure 6 The elemental distribution of the positive electrode of the pure antimony-based liquid metal battery prepared for Comparative Example 1 at 25% depth of discharge; Figure 7 The elemental distribution of the positive electrode of the antimony-based liquid metal battery in Example 2 of this invention at 25% depth of discharge; Figure 8 The image shows the appearance of the pure antimony-based liquid metal battery prepared in Comparative Example 1 after cycling. Figure 9 The appearance morphology of the antimony-based liquid metal battery prepared in Example 1 after cycling. Detailed Implementation
[0015] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings. However, the present invention is not limited to these embodiments.
[0016] Conventional liquid metal batteries consist of a negative electrode, a positive electrode, an inorganic molten salt electrolyte, a current collector, a battery casing, sealing components, and positive and negative electrode tabs. This invention introduces 20–50 mol% of highly conductive iron particles into the antimony positive electrode of the liquid metal battery. Due to the high melting point of iron (1500 °C), and considering that high processing temperatures could trigger antimony volatilization, the pretreatment temperature is controlled at 700–730 °C for 30–60 minutes to ensure that the antimony in the positive electrode fully melts and spreads at the bottom of the battery casing. The added iron, by forming a melt with the antimony, inhibits the corrosion of stainless steel by metallic antimony. Simultaneously, there is no need to introduce an inner liner into the battery casing, reducing the contact interface and contact resistance, and improving voltage efficiency. (The last sentence appears to be incomplete and possibly refers to a specific type of 14mm iron particle.) A 2mm thick lithium metal strip is wound around the negative electrode current collector to form the negative electrode assembly. Its mass is 1.05 times the mass theoretically required based on the battery capacity. This theoretical calculation assumes that the antimony in the positive electrode completely participates in the reaction after discharge, resulting in Li3Sb as the product. Considering that lithium metal is easily oxidized and consumed, a 5% excess negative electrode is used. After preparing the positive and negative electrodes, the height of the upper surface of the positive electrode from the top of the battery casing is measured using calipers. The negative electrode assembly is then assembled based on this measurement, ensuring the distance between the positive and negative electrodes is controlled at 12-15mm. Too short a distance increases the risk of short circuits, while too large a distance increases battery polarization. After the negative electrode assembly is completed, the required electrolyte mass is calculated based on the positive and negative electrode distance. The electrolyte mass is controlled to just submerge the upper surface of the negative electrode current collector. The calculation formula is m=0.8ρπr. 2(h+d), where m is the electrolyte mass, r is the battery casing radius, h is the distance between the positive and negative electrodes, d is the thickness of the negative electrode current collector, and ρ is the electrolyte density. Since the current collector itself occupies a certain volume, the actual electrolyte mass added should be 80% of the theoretical value. After confirming the required electrolyte mass, assemble the battery. After assembly, weld the positive and negative electrode tabs. The battery assembly is now complete.
[0017] Example 1 The steps for preparing an antimony-based liquid metal battery are as follows: (1) Place 0.5g of iron particles and 4.55g of antimony particles into the cleaned stainless steel battery casing as positive electrode materials; (2) The prepared cathode material was placed in a pit furnace with an inert atmosphere and heated to 730 °C at a rate of 2 °C / min and held for 30 min to prevent cathode oxidation and ensure complete melting of the cathode. After holding, the cathode was cooled with the furnace to obtain Fe-Sb cathode, wherein the Fe content was 20 mol% (3) Calculate the required amount of lithium metal according to the molar ratio of Li / Sb=3:1, and wrap the lithium metal strip around the cleaned negative electrode current collector as a negative electrode component. (4) Use a vernier caliper to measure the height of the positive electrode upper surface obtained in step (2) from the top of the battery case, and use this to calculate the height of the negative electrode assembly, and control the distance between the positive and negative electrodes to 12mm; (5) Calculate the required electrolyte mass based on the distance between the positive and negative electrodes, and weigh the pre-dehydrated and melted LiF-LiCl-LiBr electrolyte accordingly; (6) Melt the weighed electrolyte again, and use a clean spatula to remove impurities from the surface of the molten electrolyte. Then pour the molten electrolyte material into the stainless steel battery case, and then assemble the negative electrode assembly onto the stainless steel battery case. (7) After cooling, seal the top cover of the battery in an inert atmosphere and weld the positive and negative electrode tabs. After preparation, apply inorganic high-temperature resistant adhesive to the sealing parts and wait for it to solidify completely before testing.
[0018] Example 2 The steps for preparing an antimony-based liquid metal battery are as follows: (1) Weigh 1.0g of iron particles and 4.55g of antimony particles into the cleaned stainless steel battery casing as the positive electrode; (2) The prepared positive electrode was placed in a pit furnace with an inert atmosphere and heated to 730°C at a rate of 2°C / min and held for 30 min to prevent oxidation of the positive electrode and ensure that the positive electrode was fully melted. After the holding period, the electrode was cooled with the furnace to obtain the Fe-Sb positive electrode, in which the Fe content was 33 mol%. (3) Calculate the required amount of lithium metal according to the molar ratio of Li / Sb=3:1, and wrap the lithium metal strip around the cleaned negative electrode current collector as a negative electrode component; (4) Use a vernier caliper to measure the height of the positive electrode upper surface obtained in step (2) from the top of the battery case, and use this to calculate the height of the negative electrode assembly, and control the distance between the positive and negative electrodes to 12mm; (5) Calculate the required electrolyte mass based on the distance between the positive and negative electrodes, and weigh the pre-dehydrated and melted LiF-LiCl-LiBr electrolyte accordingly; (6) Melt the weighed electrolyte again, and use a clean spatula to remove the impurities on the surface of the molten electrolyte. Then pour the molten electrolyte material into the stainless steel battery case, and then assemble the negative electrode assembly onto the stainless steel battery case. (7) After cooling, seal the top cover of the battery in an inert atmosphere and weld the positive and negative electrode tabs. After preparation, apply inorganic high-temperature resistant adhesive to the sealing parts and wait for it to solidify completely before testing.
[0019] Example 3 The steps for preparing an antimony-based liquid metal battery are as follows: (1) Weigh 2.0g of iron particles and 4.55g of antimony particles into the cleaned stainless steel battery casing as the positive electrode; (2) The prepared positive electrode was placed in a pit furnace with an inert atmosphere and heated to 730°C at a rate of 2°C / min and held for 30 min to prevent oxidation of the positive electrode and ensure that the positive electrode was fully melted. After the holding period, the electrode was cooled with the furnace to obtain the Fe-Sb positive electrode, in which the Fe content was 50 mol%. (3) Calculate the required amount of lithium metal according to the molar ratio of Li / Sb=3:1, and wrap the lithium metal strip around the cleaned negative electrode current collector as a negative electrode component; (4) Use a vernier caliper to measure the height of the positive electrode upper surface obtained in step (2) from the top of the battery case, and use this to calculate the height of the negative electrode assembly, and control the distance between the positive and negative electrodes to 12mm; (5) Calculate the required electrolyte mass based on the distance between the positive and negative electrodes, and weigh the pre-dehydrated and melted LiF-LiCl-LiBr electrolyte accordingly; (6) Melt the weighed electrolyte again, and use a clean spatula to remove impurities from the surface of the molten electrolyte. Then pour the molten electrolyte material into the stainless steel battery case, and then assemble the negative electrode assembly onto the stainless steel battery case. (7) After cooling, seal the top cover of the battery in an inert atmosphere and weld the positive and negative electrode tabs. After preparation, apply inorganic high-temperature resistant adhesive to the sealing parts and wait for it to solidify completely before testing.
[0020] Comparative Example 1 Preparation of pure antimony-based liquid metal batteries Iron particles were removed from the positive electrode material, i.e., 4.55g of antimony particles were used as the positive electrode material, and everything else was the same as in Example 1.
[0021] Figure 1 The battery performance of the antimony-based liquid metal batteries prepared in Examples 1-3 shows that, under the same current conditions, compared to the pure antimony-based liquid metal battery prepared in Comparative Example 1, introducing a small amount of iron into the positive electrode can significantly improve the battery voltage efficiency. When the iron content increases from 20 mol% to 33 mol%, the battery voltage efficiency further improves. However, when the iron content further increases to 50 mol%, although the battery voltage efficiency is still higher than that of the pure antimony-based battery, it decreases compared to the battery with 33 mol% iron content. This indicates that the iron content is excessive, which actually causes performance degradation.
[0022] Figure 2 The long-cycle performance of the antimony-based liquid metal battery prepared in Example 1; Figure 3 The long-cycle performance of the antimony-based liquid metal battery prepared in Example 2; Figure 4 The long-cycle performance of the antimony-based liquid metal battery prepared in Example 3; Figure 5 To demonstrate the long-cycle performance of the pure antimony-based liquid metal battery prepared in Comparative Example 1; Figure 8 The image shows the appearance of the pure antimony-based liquid metal battery prepared in Comparative Example 1 after cycling. Figure 9 The appearance morphology of the antimony-based liquid metal battery prepared in Example 1 after cycling.
[0023] Combination Figures 2 to 4 It can be observed that the battery capacity is around 3Ah, and the active antimony in this embodiment contributes 3Ah to the capacity. Figure 5 The capacity of a pure antimony-based battery without added iron is also around 3Ah, indicating that the added iron does not participate in the electrochemical reaction and contribute to the capacity.
[0024] Depend on Figures 2 to 4 As can be seen, the method proposed in this invention can significantly improve battery stability; the battery capacity remains unchanged after hundreds of cycles, and from... Figure 9 The battery appeared normal after cycling. Figure 5 The pure antimony-based liquid metal battery prepared in Comparative Example 1 began to decay in discharge capacity and gradually decreased in coulombic efficiency after approximately 80 cycles. During observation... Figure 8 Upon inspection of the battery's exterior, obvious spots due to corrosion were observed on the outer surface of the battery casing, indicating a slight leakage. These results further demonstrate the effectiveness of the present invention.
[0025] Figure 6 The elemental distribution of the positive electrode of the pure antimony-based liquid metal battery prepared for Comparative Example 1 at a 25% depth of discharge is shown. It can be seen that the pure antimony-based positive electrode is generally concentrated at the bottom of the battery casing. The reaction starts from the interface between the positive electrode and the electrolyte, and there is electrolyte infiltration between the positive electrode and the battery casing, which increases the contact resistance between the positive electrode and the battery casing. This is also an important reason affecting the battery voltage efficiency.
[0026] Figure 7 This is the elemental distribution of the positive electrode of the antimony-based liquid metal battery in Example 2 of the present invention at a depth of discharge of 25%; [The remaining text appears to be a fragment and requires further context for accurate translation.] Figure 7 Based on the pretreatment method of the positive electrode in this invention, the added iron particles are dispersed in the positive electrode in solid form, forming an "antimony-coated iron" melt structure. Simultaneously, due to the density difference of the solids, the positive electrode cannot completely aggregate, thus forming channels in the upper layer. The electrolyte can penetrate into the positive electrode melt along these channels, increasing the contact area with the positive electrode active material and thus reducing polarization. Furthermore, the addition of iron can "capture" antimony, thereby to some extent "inhibiting" antimony from directly reacting with the battery casing and improving battery stability.
[0027] For any points not covered above, existing technologies shall apply.
[0028] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an antimony-based liquid metal battery, characterized in that, Includes the following steps: S1. Place a mixture of iron particles and antimony particles in a stainless steel battery casing as the positive electrode material, and then keep it at 700-730 ℃ in an inert atmosphere for a period of time to ensure that the positive electrode material is fully melted and spread at the bottom of the battery casing. After the heat preservation is completed, cool it with the furnace to obtain the Fe-Sb positive electrode. S2. Melt the electrolyte material by heating and pour it into the stainless steel battery casing; S3. Assemble the negative electrode current collector loaded with metallic lithium and the battery top cover onto the stainless steel battery casing, and then allow it to cool naturally; wherein the battery top cover and the stainless steel battery casing cooperate to form a closed space.
2. The preparation method according to claim 1, characterized in that, The iron particles are 20-50 mol of a mixture of iron and antimony particles.
3. The preparation method according to claim 1, characterized in that, The distance between the positive and negative electrodes is controlled at 12–15 mm.
4. The preparation method according to claim 1, characterized in that, The negative electrode current collector loaded with lithium metal is 14 mm A 2mm thick lithium metal strip is wound around the negative electrode current collector.
5. The preparation method according to claim 5, characterized in that, Calculate the required amount of metallic lithium based on the Li / Sb molar ratio of 3:
1.
6. The preparation method according to claim 5, characterized in that, Keep warm at 700–730 °C in an inert atmosphere for 30–60 min.
7. The preparation method according to claim 1, characterized in that, The required electrolyte mass is calculated based on the distance between the positive and negative electrodes. The electrolyte mass is controlled to just submerge the upper surface of the negative electrode current collector. The calculation formula is m = 0.8ρπr 2 (h+d), where m is the electrolyte mass, the stainless steel battery casing is cylindrical, r is the battery casing radius, h is the distance between the positive and negative electrodes, d is the thickness of the negative electrode current collector, and ρ is the electrolyte density. Since the current collector itself occupies a certain volume, the actual added electrolyte mass is 80% of the theoretical value.
8. An antimony-based liquid metal battery prepared by the preparation method according to any one of claims 1-8.
